Justification for Domestic Violence and Women’s Autonomy in Zambia - Mengo, Cecilia; Pillai, Vijayan (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
Background: In many African countries, cultural practices along with deteriorating economic conditions have resulted increases in the number of cases of domestic violence. Furthermore, high levels of gender equality has contributed to a normative climate of acceptance and justification of domestic violence. The primary purpose of this study is to examine the relationship between women’s autonomy and justification for domestic violence among women in Zambia. Method: The Demographic Health Survey (DHS) data for Zambia (2008) was used. Confirmatory factor analysis (CFA) was conducted to develop a scale of women’s autonomy. Logistic regression was conducted to examine the predictors of justification for domestic violence. Results: Logistic regression results show that two indicators of women’s autonomy, low levels of education and high degree of spouse control significantly increase the odds of justification for domestic violence. Conclusion: The scale developed in this study to measure women’s autonomy in Zambia will have to be validated for several other African countries. The items that constitute the scale suggest directions for interventions to empower women.
Keywords: developing countries